Predictors of post-concussion symptom severity in a university-based concussion clinic. (21st March 2019) - Houck, Zac; Asken, Breton; Bauer, Russell; Clugston, James
ABSTRACT: Objective : To investigate potential predictors of acute post-concussion symptom severity in a university population. Methods : Data were obtained from the University of Florida Student Health Care Center Concussion Databank. Symptom severity, measured by the Sport Concussion Assessment Tool – third edition Symptom Evaluation (S3SE), was analyzed at 0–3 (n = 99) and 7–14 days (n = 56) post-concussion. Participants were 99 (56 females; age range: 18–30) students from the University of Florida who had been referred to the center's Concussion Clinic. Independent samples t-test and Mann–Whitney U were used to assess group differences in overall and domain-specific symptom severity, respectively. Hierarchical regressions were used to assess predictors of symptom severity at 0–3 and 7–14 days, as well as residual symptom change between time points. Results : Female sex (β = .293; p = .002) and history of ADHD (β = .312; p = .001) predicted greater symptom severity at 0–3 days. History of motion sickness predicted lower symptom severity (β = −.199; p = .033). ADHD (β = .284; p = .009) and higher 0–3-day physical symptoms (β = .552; p < .001) predicted greater symptom severity at 7–14 days. ADHD predicted residual symptom severity change between time points (β = .433; p = .001). Conclusion : ADHD, female sex, and acute physical symptoms (0–3 days) represent risk factors for greater symptom severity in the first two weeks post-concussion among college students.